THE IMPACTS OF GREEN MARKETING AWARENESS ON PURCHASE INTENTIONS OF STARBUCKS IN SEMARANG - Forma Nastiti, Monica Rizka; Indriani, Farida (Diponegoro Journal of Management, 2021)
This research aims to examine perceptions of corporate social responsibility and product image as a mediating variable in the consumer green marketing awareness variable and consumer purchase intentions in Starbucks consumers in Semarang. This research will be conducted using questionnaire methods. The object of the research is 120 consumers of PT Sari Coffee Indonesia or Starbucks Indonesia products in Semarang City who had purchased Starbucks products more than twice a month. Data analyzed using IBM SPSS 22 program. The results showed that the consumer green marketing awareness was confirmed as the leading factor that positively influence consumer purchase intentions. While the perceptions of corporate social responsibility and product image partially mediate consumer green marketing awareness and consumer purchase intentions.